STRATEGI PERENCANAAN D’OZ RADIO BALI PADA PROGRAM OZ BALIHOP - Cahaya Pratiwi, Komang Putri; Pascarani, Ni Nyoman Dewi; Purnawan, Ni Luh Ramaswati (E-Jurnal Medium, 2018)
ABSTRACT The increasingly competitive radio competition encourages D'OZ Radio Bali to make a new program to improving their benefits materially company. OZ BALIHOP (Bali Places Hang Out) then present and become the new program D'OZ Radio Bali. The purpose of this research is to know the strategy of planning the Bali Radio program on D'OZ OZ BALIHOP. This research uses the concept of the planning program that is part of the strategic management aspects of the programs broadcast by the SWOT analysis. This type of research is qualitative. Informants are chosen using a purposive technique. The data obtained through interviews. Data analysis techniques used are interactive models by Miles and Huberman. The results showed that the strategy of planning the Bali Radio program on D'OZ OZ BALIHOP is a strategy SO (Strengths – Opportunities) that is a strategy that maximizes the strength owned by exploiting the opportunities that exist. SO the strategy conducted by D'OZ Radio Bali is creating new program OZ BALIHOP with different broadcasting technique with other radio programs especially in Bali, understand the characteristics of their listener with some researches the new place with regard to the content of the broadcasts of OZ BALIHOP to expand the range of broadcast content that discusses about the culinary and lifestyle. Then give the space for listeners who do not listen to OZ BALIHOP OZ directly through the creation of special programs OZ BALIHOP instagram, and then after the program runs also conducted an evaluation regarding the response of listeners at a certain period to optimize the amount of listeners so that the purpose of this new programs OZ BALIHOP to getting listeners and materially benefit can also be achieved.  Keywords: D’OZ Radio Bali, OZ BALIHOP, SWOT Analysis, Strategy Planning Programs .